France : 2012 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2012)
The 2012 Article IV Consultation with France discusses the financial and economic conditions of the country. Although France weathered the 2008 financial and subsequent euro area crises relatively well compared with other advanced countries, its recovery has been sluggish. France has become a less open economy and reported a steady loss of export market share relative to its European peers. The current challenge for France is to pursue fiscal policy consolidation that balances cyclical considerations with the need to preserve market confidence in French policies and in the euro area crisis resolution strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet